The constitution and administrative ethics in America - Richardson, William D; Lloyd G
This essay explores the contributions of founding thought to current issues regarding administrative ethics. It is argued that founders understood public administration to be a political enterprise and, therefore, public administrators should not be excluded from their analysis of citizen character the U.S. constitution anticipates that self-interest will be the dominant motive of citizens and governors, including public administrators. However, the founders hoped that it would encourage the emergence of virtuous and disinterested public servants. The contemporary literature on administrative ethics reflects these concerns through two different characterizations: the disinterested administrator and the self-
Keywords: Constitutions - USA; Ethics